Letter: the Shock Index and predicting outcomes in patients with upper gastrointestinal bleeding. Issue 2 (26th December 2019) - McPherson, Simon J; Hammond, Christopher J
Abstract : LINKED CONTENT This article is linked to Saffouri et al and Stanley papers. To view these articles, visit https://doi.org/10.1111/apt.15541 and https://doi.org/10.1111/apt.15615 .